Richter’s Hernia: A Case Report - Nazir, Shahid; Sulman, Sahrish; Munir, Ambreen; Kumari, Aneeta; Rehmat, Sehrish Shah (Journal of Liaquat University of Medical & Health Sciences, 2019)
Richter’s hernia (partial enterocele) is rare disease in which there is a swelling or/and entrapment of a small part of intestine along its antimesenteric border due to minor defect in abdominal wall. Diagnosis of Richter’s hernia & their associated complications are difficult due to absence of obstructive symptoms with presence of early strangulation thereby increases mortality to 20-60%. For early diagnosis of Richter’s hernia ultrasonography and computed tomography (CT) are utilized and emergency surgery is necessary to obviate complications of disease. Here, we are presenting a case of 20-year male patient reporting for abdominal pain radiating to right hypochondria, anorexia and low-grade fever for 24 hours in which an incidental diagnosis of Richter’s Hernia along with acute appendicitis was made.